Comparing immunological and molecular tests with conventional methods in diagnosis of acute invasive fungal rhinosinusitis - Badiee, Parisa; Moghadami, Mohsen; Rozbehani, Hossain (The Journal of Infection in Developing Countries, 2016)
Introduction: This study compared immunological and molecular testswith conventional methods in the diagnosis of acute invasive fungal rhinosinusitis. Methodology: All tissue samples from maxillary sinuses were cultured and stained using periodic acid-Schiff. Two blood samples were cultured by bedside inoculation into BACTEC medium. Diagnostic tests were used: enzyme-linked immunosorbent assay for detection of galactomannan and mannan in serum samples, real-time PCR assays for Aspergillus spp. and Candida spp., and nested PCR for the Mucoraceae family. Results: Among 31 immunocompromised patients, based on host factors, clinical, radiological and mycological findings, 18 patients were diagnosed with documented infection. By direct smear examination, 9 patients (50%) had positive results for Mucoraceae family, but only 5 samples showed growth in the culture (55.5%). Nested PCR results for species in this family were negative in all serum samples from patients. In addition, 9 patients had positive direct microscopic findings, of which 7 specimens produced positive growth for Aspergillus flavus (77.7%). The galactomannan test was positive in 6/9 (66.6%), and Aspergillus PCR were positive in 6 patients (66.6%). The isolated agent was C. albicans in one patient. The mannan antigen test to detect Candida was negative. None of the blood cultures was positive for fungal infection. Conclusions: The efficient method to diagnose fungal rhinosinusitis was direct microscopic examination of tissue samples. Immunological and molecular methods, which are available for some important fungi, can help clinicians with the diagnosis and management of infections in patients in critical condition when tissue sampling is not available.